Effect of nanoparticle shape on therapeutic temperature distribution during magnetic hyperthermia. (4th February 2021) - Tang, Yundong; Flesch, Rodolfo C C; Jin, Tao; Gao, Yueming; He, Minhua
Abstract: Treatment temperature distribution is a crucial factor for magnetic hyperthermia, since it directly determines the treatment effect related to the apoptosis situation of malignant cells. The shape of magnetic nanoparticles (MNPs) is one of many factors that can affect the treatment temperature during therapy. This paper conducts a comparative study on three different shapes of MNPs by considering the effective area percentage of treatment temperature distribution. The treatment temperature for a proposed model is predicted by solving bio-heat transfer equations, which take the power dissipation of MNPs as the input and consider a temperature-dependent blood perfusion rate in these equations at the same time. The simulation results demonstrate that the treatment temperature distribution can be effectively improved when the temperature-dependent blood perfusion rate is used for the simulation with respect to a constant case. In addition, the MNPs with higher regular shape can lead to a better result than a lower case in the treatment temperature distribution when the same condition is considered for therapy.